2016
DOI: 10.1007/s13258-016-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Identification of inducible proteins in the phenanthrene degrader Sphingobium chungbukense DJ77 by 2-dimensional electrophoresis and liquid chromatography/tandem mass spectrometry

Abstract: Due to the change in the naming convention of Sphingomonas chungbukensis DJ77 to Sphingobium chungbukense DJ77, the title of the article is updated to ''Identification of inducible proteins in the phenanthrene degrader Sphingobium chungbukense DJ77 by 2-dimensional electrophoresis and liquid chromatography/tandem mass spectrometry''.The online version of the original article can be found under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…3) and found that these five proteins have multiple functionality. First, BphB (X1) catalyzes the NAD + -dependent oxidation of trans-dihydrodiols [2], and PhnQ (X2) cleaves aromatic rings in three PNB catabolic branches [1]. BphD (X3) is capable of degrading polychlorinated biphenyls as well as biphenyl itself [18] so that the biphenyl branch splits into two different routes.…”
Section: Predicted Proteins Involved In Multiple Catabolic Pathways Fmentioning
confidence: 99%
“…3) and found that these five proteins have multiple functionality. First, BphB (X1) catalyzes the NAD + -dependent oxidation of trans-dihydrodiols [2], and PhnQ (X2) cleaves aromatic rings in three PNB catabolic branches [1]. BphD (X3) is capable of degrading polychlorinated biphenyls as well as biphenyl itself [18] so that the biphenyl branch splits into two different routes.…”
Section: Predicted Proteins Involved In Multiple Catabolic Pathways Fmentioning
confidence: 99%